Pengaruh Kecerdasan Emosional terhadap Penyesuaian Sosial Mahasiswa Baru IAKN Kupang Baru - Marleny Rambu Riada; Irene Elvira Daik; Ferderika Leuanan (Universitas Jabal Ghafur, 2022)
ABSTRACTThis study aims to determine the effect of emotional intelligence on the social adjustment of IAKN Kupang students during the covid 19 pandemic. The research method used is quantitative. The sample of this study amounted to 95 semester 1 students of the Faculty of Social Sciences and Christian Religion who were selected using the non-probability sampling method with purposive sampling technique. Data were collected using the Goleman emotional intelligence scale and the Scheneider social adjustment. Data analysis using simple regression analysis technique. The results showed that the calculated F value was 69.774 with a significance of 0.000 (p 0.05), which means that there is an influence of emotional intelligence on students' social adjustment. The contribution of the emotional intelligence variable is seen in the R Square value of 0.429, meaning that 42.9% of first semester students' social adjustment during covid 19 was influenced by emotional intelligenceKeywords : emotional intelligence, social adjustment, student, covid-19 ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional terhadap penyesuaian sosial mahasiswa IAKN Kupang selama pandemi covid 19. Metode penelitian yang digunakan adalah kuantitatif. Sampel penelitian ini berjumlah 95 orang mahasiswa semester 1 Fakultas Ilmu Sosial dan keagamaan Kristen yang dipilih dengan menggunakan metode nonprobality Sampling dengan teknik purposive sampling. Data dikumpulkan menggunakan skala kecerdasan emosional Goleman dan penyesuaian sosial Scheneider. Analisis data menggunakan teknik analisis regresi sederhana. Hasil penelitian menunjukkan nilai F hitung sebesar 69,774 dengan signifikansi sebesar 0,000 (p0.05) yang berarti ada pengaruh kecerdasan emosional terhadap penyesuaian sosial mahasiswa. Sumbangan variabel kecerdasan emosional dilihat pada nilai R Square sebesar 0.429 artinya 42,9 % penyesuaian sosial mahasiswa semester 1 selama covid 19 dipengaruhi kecerdasan emosional. Kata kunci: kecerdasan emosional, penyesuaian sosial, mahasiswa , covid 19